2014
DOI: 10.1515/plm-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical tomography to monitor the photocoagulation front during interstitial photothermal therapy: Numerical simulations and measurements in tissue-simulating phantoms

Abstract: Near-infrared interstitial photothermal therapy (PTT) is currently undergoing clinical trials as an alternative to watchful waiting or radical treatments in patients with low/intermediate-risk focal prostate cancer. Currently, magnetic resonance imaging (MRI)-based thermography is used to monitor thermal energy delivery and determine indirectly the completeness of the target tumor destruction while avoiding damage to adjacent normal tissues, particularly the rectal wall. As an alternative, transrectal diffuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…We previously used the transrectal probe DOT system of Piao et al 17 to measure tissue-simulating phantoms containing different sizes of highly scattering cylindrical inclusions, as well as numerical simulations using finite element calculations based on the diffusion equation. 16 This study demonstrated the sensitivity of the DOT signals to the diameter of the inclusion and, hence, of the distance between the nearest inclusion boundary and the DOT source-detector array. Multiple DOT source-detector configurations were simulated to determine the geometries with the highest location sensitivity.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…We previously used the transrectal probe DOT system of Piao et al 17 to measure tissue-simulating phantoms containing different sizes of highly scattering cylindrical inclusions, as well as numerical simulations using finite element calculations based on the diffusion equation. 16 This study demonstrated the sensitivity of the DOT signals to the diameter of the inclusion and, hence, of the distance between the nearest inclusion boundary and the DOT source-detector array. Multiple DOT source-detector configurations were simulated to determine the geometries with the highest location sensitivity.…”
Section: Introductionmentioning
confidence: 72%
“…We are developing a transrectal diffuse optical tomography (DOT) system as a method for assessing the location and size of the photothermal lesion(s) in near-real time, based primarily on changes in light scattering that are associated with coagulation. 15,16 The clinical objective is to track the location of the boundary of the growing coagulation zone, which is typically sharply delineated. The posterior border of the coagulation zone is particularly important because of the risk of damage to the rectal wall; thus, we have set an accuracy of AE1 mm for localization of this border, based on clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…3(b) shows a cross section of the phantom CT image obtained from the dedicated breast cancer CT scanner. As described in the numerical simulation, we have performed the DOT reconstruction of this phantom experiment without the structural prior, with the structural prior through the method of soft prior, and with the structural guidance by the proposed kernel method of 12 different cases with 3 different nearest neighbor k (16,32,64) and 4 different voxel numbers (3×3×3, 5×5×5, 7×7×7, and 9×9×9). The reconstructed optical absorption coefficient images are plotted in Fig.…”
Section: Phantom Experimental Resultsmentioning
confidence: 99%
“…The lengths of the feature vector were 27, 125, 343, and 729, respectively. For knnsearch, three different values of k (16,32,64), the number of nearest neighbors, were also studied. To evaluate and compare the quality of the reconstructed DOT images quantitatively, we used a combination of 4 metrics listed below.…”
Section: Optimization Of the Kernel Methodsmentioning
confidence: 99%
See 1 more Smart Citation